Holocene development and climatic sensitivity of an Amazonian peatland pole forest: Nueva York, Peru - Christine M. Åkesson; Katherine H. Roucoux; Arnoud Boom; Greta C. Dargie; Jhon del Aguila-Pasquel; Gerardo Flores; Pauline Gulliver; William Hiles; Timothy R. Baker; Frederick C. Draper; Adam Hastie; Eurídice N. Honorio Coronado; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Monitoring water level dynamics in neotropical peatlands with earth observation data - Antje Uhde; Laura L. Hess; Alison M. Hoyt; Christiane Schmullius; Euridice N. Honorio Coronado; Edmundo Mendoza Olmos; Gerardo Flores Llampazo; Susan Trumbore; Timothy Baker; Juan S. Hernandez Suarez; Oliver L. Phillips; Frederick C. Draper; et al. (Remote Sensing of Environment, 2026)

Sustainable management of non-timber forest products in Peruvian Amazonia: lessons learnt from participatory use of smartphone technology - Charlotte E. Wheeler; Althea L. Davies; Luis Andueza; Lydia E.S. Cole; Nállarett Dávila; Jhon Del Águila; Margarita del Aguila Villacorta; Frederick C. Draper; Charlotte L.D. Evans; Eurídice N. Honorio Coronado; Nina Laurie; Eva Loja; et al. (Journal of Environmental Management, 2025)

Net primary productivity and litter decomposition rates in two distinct Amazonian peatlands - G. C. Dargie; J. del Aguila‐Pasquel; C. J. Córdova Oroche; J. Irarica Pacaya; J. Reyna Huaymacari; T. R. Baker; A. Hastie; E. N. Honorio Coronado; S. L. Lewis; K. H. Roucoux; E. T. Mitchard; M. Williams; et al. (Global Change Biology, 2024)
Measurements of net primary productivity (NPP) and litter decomposition from tropical peatlands are severely lacking, limiting our ability to parameterise and validate models of tropical peatland development and thereby make robust predictions of how these systems will respond to future environmental and climatic change. Here, we present total NPP (i.e., above‐ and below‐ground) and decomposition data from two floristically and structurally distinct forested peatland sites within the Pastaza Marañón Foreland Basin, northern Peru, the largest tropical peatland area in Amazonia: (1) a palm (largely Mauritia flexuosa ) dominated swamp forest and (2) a hardwood dominated swamp forest (known as ‘pole forest’, due to the abundance of thin‐stemmed trees). Total NPP in the palm forest and hardwood‐dominated forest (9.83 ± 1.43 and 7.34 ± 0.84 Mg C ha −1 year −1 , respectively) was low compared with values reported for terra firme forest in the region (14.21–15.01 Mg C ha −1 year −1 ) and for tropical peatlands elsewhere (11.06 and 13.20 Mg C ha −1 year −1 ). Despite the similar total NPP of the two forest types, there were considerable differences in the distribution of NPP. Fine root NPP was seven times higher in the palm forest (4.56 ± 1.05 Mg C ha −1 year −1 ) than in the hardwood forest (0.61 ± 0.22 Mg C ha −1 year −1 ). Above‐ground palm NPP, a frequently overlooked component, made large contributions to total NPP in the palm‐dominated forest, accounting for 41% (14% in the hardwood‐dominated forest). Conversely, Mauritia flexuosa litter decomposition rates were the same in both plots: highest for leaf material, followed by root and then stem material (21%, 77% and 86% of mass remaining after 1 year respectively for both plots). Our results suggest potential differences in these two peatland types' responses to climate and other environmental changes and will assist in future modelling studies of these systems.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Unpacking the diversity of monoterpene oxidation pathways via nitrooxy–alkyl radical ring-opening reactions and nitrooxy–alkoxyl radical bond scissions - Danielle Draper; Thomas Golin Almeida; Siddharth Iyer; James N. Smith; Theo Kurtén; Nanna Myllys (Journal of Aerosol Science, 2024)

The socioecological benefits and consequences of oil palm cultivation in its native range: The Sustainable Oil Palm in West Africa (SOPWA) Project - Michael D. Pashkevich; Cicely A.M. Marshall; Benedictus Freeman; Valentine J. Reiss-Woolever; Jean-Pierre Caliman; Julia Drewer; Becky Heath; Matthew T. Hendren; Ari Saputra; Jake Stone; Jonathan H. Timperley; William Draper; et al. (Science of The Total Environment, 2024)

Understanding different dominance patterns in western Amazonian forests - Laura Matas‐Granados; Frederick C. Draper; Luis Cayuela; Julia G. de Aledo; Gabriel Arellano; Celina Ben Saadi; Timothy R. Baker; Oliver L. Phillips; Eurídice N. Honorio Coronado; Kalle Ruokolainen; Roosevelt García‐Villacorta; Katherine H. Roucoux; et al. (Ecology Letters, 2024)
Dominance of neotropical tree communities by a few species is widely documented, but dominant trees show a variety of distributional patterns still poorly understood. Here, we used 503 forest inventory plots (93,719 individuals ≥2.5 cm diameter, 2609 species) to explore the relationships between local abundance, regional frequency and spatial aggregation of dominant species in four main habitat types in western Amazonia. Although the abundance‐occupancy relationship is positive for the full dataset, we found that among dominant Amazonian tree species, there is a strong negative relationship between local abundance and regional frequency and/or spatial aggregation across habitat types. Our findings suggest an ecological trade‐off whereby dominant species can be locally abundant ( local dominants ) or regionally widespread ( widespread dominants ), but rarely both ( oligarchs ). Given the importance of dominant species as drivers of diversity and ecosystem functioning, unravelling different dominance patterns is a research priority to direct conservation efforts in Amazonian forests.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Dominant tree species drive beta diversity patterns in western Amazonia - Frederick C. Draper; Gregory P. Asner; Eurídice N. Honorio Coronado; Timothy R. Baker; Roosevelt García‐Villacorta; Nigel C. A. Pitman; Paul V. A. Fine; Oliver L. Phillips; Ricardo Zárate Gómez; Carlos A. Amasifuén Guerra; Manuel Flores Arévalo; Rodolfo Vásquez Martínez; et al. (Ecology, 2019)
The forests of western Amazonia are among the most diverse tree communities on Earth, yet this exceptional diversity is distributed highly unevenly within and among communities. In particular, a small number of dominant species account for the majority of individuals, whereas the large majority of species are locally and regionally extremely scarce. By definition, dominant species contribute little to local species richness (alpha diversity), yet the importance of dominant species in structuring patterns of spatial floristic turnover (beta diversity) has not been investigated. Here, using a network of 207 forest inventory plots, we explore the role of dominant species in determining regional patterns of beta diversity (community‐level floristic turnover and distance‐decay relationships) across a range of habitat types in northern lowland Peru. Of the 2,031 recorded species in our data set, only 99 of them accounted for 50% of individuals. Using these 99 species, it was possible to reconstruct the overall features of regional beta diversity patterns, including the location and dispersion of habitat types in multivariate space, and distance‐decay relationships. In fact, our analysis demonstrated that regional patterns of beta diversity were better maintained by the 99 dominant species than by the 1,932 others, whether quantified using species‐abundance data or species presence–absence data. Our results reveal that dominant species are normally common only in a single forest type. Therefore, dominant species play a key role in structuring western Amazonian tree communities, which in turn has important implications, both practically for designing effective protected areas, and more generally for understanding the determinants of beta diversity patterns.

Improving estimates of tropical peatland area, carbon storage, and greenhouse gas fluxes - I. T. Lawson; T. J. Kelly; P. Aplin; A. Boom; G. Dargie; F. C. H. Draper; P. N. Z. B. P. Hassan; J. Hoyos-Santillan; J. Kaduk; D. Large; W. Murphy; S. E. Page; et al. (Wetlands Ecology and Management, 2015)

Epiphytic bryophyte flora in dry environments from the Western Mediterranean: The special case of Sierra Alhamilla (Almería, South‐eastern Spain) - V. Mazimpaka; N. G. Medina; I. Draper; F. Lara (Plant Biosystems, 2009)

Effect of creatine supplementation and sleep deprivation, with mild exercise, on cognitive and psychomotor performance, mood state, and plasma concentrations of catecholamines and cortisol - T. McMorris; R. C. Harris; J. Swain; J. Corbett; K. Collard; R. J. Dyson; L. Dye; C. Hodgson; N. Draper (Psychopharmacology, 2006)